MENTAL FORAMEN POSITION ON PANORAMIC RADIOGRAPHS OF PATIENTS AGED 20-44 YEARS BASED ON GENDER AT RSGM UNJANI - Mutiara Sukma Suntana; Tichvy Tammama; Nabilla Mulya Kurniawan (Journal of Health and Dental Sciences, 2023)
The mental foramen is a small hole located in the body of the mandible in the premolar to molar region. There are veins, arteries, and a branch of the inferior nervus alveolaris, the nervus mentalis. The blood vessels and nerves in the mental foramen supply and innervate the lower lip region, gingiva, soft tissues of the chin, and lower teeth. Various factors influence the development of the mental foramen, such as race, age, gender, and ethnicity. Determination of the position of the mental foramen can help in diagnosis, treatment, and some clinical measures related to the mental foramen. This study aims to determine the difference in the position of the mental foramen according to gender and the difference in the position of the right and left mental foramen according to gender in patients at RSGM Unjani. This study was conducted using an analytical method with a cross-sectional approach. The research object was 44 panoramic radiographs taken with a purposive sampling technique. To analyze the difference in the position of the mental foramen according to gender, the study used the Mann-Whitney test, while to analyze the difference in the right and left positions according to gender; we used the Chi-Square test. The results showed no significant difference in the position of the mental foramen towards gender (p>0.05). There was no significant difference in the position of the mental foramen between the left and right on the panoramic radiograph of the patient according to gender (p>0.05). The most common position was in line with the lower second premolar with a percentage of 62.5%, and the position of the mental foramen was symmetrical both left and right with a percentage of 52.3%. It can be concluded that there is no significant difference between the position of the mental foramen and gender on panoramic radiographs of patients aged 20–44 years at RSGM Unjani in 2021. DOI : 10.54052/jhds.v3n2.p169-182